Purine Permease-Type Benzylisoquinoline Alkaloid Transporters in Opium Poppy. Issue 3 (29th August 2019) - Dastmalchi, Mehran; Chang, Limei; Chen, Rongji; Yu, Lisa; Chen, Xue; Hagel, Jillian M.; Facchini, Peter J.
Abstract : The study of a family of alkaloid transporters in opium poppy shows a key role for alkaloid uptake in yeast strains engineered to produce opiate alkaloids. Abstract: Although opiate biosynthesis has been largely elucidated, and cell-to-cell transport has been long postulated, benzylisoquinoline alkaloid (BIA) transporters from opium poppy ( Papaver somniferum ) have not been reported. Investigation of a purine permease-type sequence within a recently discovered opiate biosynthetic gene cluster led to the discovery of a family of nine homologs designated as BIA uptake permeases (BUPs). Initial expression studies in engineered yeast hosting segments of the opiate pathway showed that six of the nine BUP homologs facilitated dramatic increases in alkaloid yields. Closer examination revealed the ability to uptake a variety of BIAs and certain pathway precursors (e.g. dopamine), with each BUP displaying a unique substrate acceptance profile. Improvements in uptake for yeast expressing specific BUPs versus those devoid of the heterologous transporters were high for early intermediates (300- and 25-fold for dopamine and norcoclaurine, respectively), central pathway metabolites [10-fold for ( S )-reticuline], and end products (30-fold for codeine). A coculture of three yeast strains, each harboring a different consecutive segment of the opiate pathway and BUP1, was able to convert exogenous Levodopa to 3 ± 4 mg/L codeine via a 14-step bioconversion process involving over a dozen enzymes. BUP1 is highly expressed in opium poppy latex and is localized to the plasma membrane. The discovery of the BUP transporter family expands the role of purine permease-type transporters in specialized metabolism, and provides key insight into the cellular mechanisms involved in opiate alkaloid biosynthesis in opium poppy.